2017
DOI: 10.1007/s13337-017-0390-8
|View full text |Cite
|
Sign up to set email alerts
|

History and current trends in influenza virus infections with special reference to Sri Lanka

Abstract: The World Health Organization (WHO) estimates that approximately one billion people are infected and up to 500,000 people die from influenza each year in the world. Influenza is considered to be the greatest killer of the human populations, due to the 1918 Spanish flu, which killed millions around the world. Despite the effective treatment available against influenza, it still contributes to significant morbidity and mortality. Currently circulating influenza strains in humans include influenza A (H1N1)pdm09, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 52 publications
1
30
0
1
Order By: Relevance
“…1,3 Research has shown that nineteen of the genetically distinct types have shown reassortment since the 1918 Spanish flu which ravaged the world and claimed over 20-50 million lives globally. 1,4 Additionally, six strains of the genetically distinct subtypes are known to have human-to-human transmission, ten are zoonotic avian influenza viruses while three are zoonotic swine influenza viruses. 1,3,4 However, in the past five years, four novel influenza subtypes and three novel strains of the virus have emerged in humans.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3 Research has shown that nineteen of the genetically distinct types have shown reassortment since the 1918 Spanish flu which ravaged the world and claimed over 20-50 million lives globally. 1,4 Additionally, six strains of the genetically distinct subtypes are known to have human-to-human transmission, ten are zoonotic avian influenza viruses while three are zoonotic swine influenza viruses. 1,3,4 However, in the past five years, four novel influenza subtypes and three novel strains of the virus have emerged in humans.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Additionally, six strains of the genetically distinct subtypes are known to have human-to-human transmission, ten are zoonotic avian influenza viruses while three are zoonotic swine influenza viruses. 1,3,4 However, in the past five years, four novel influenza subtypes and three novel strains of the virus have emerged in humans. [1][2][3][4] Although fourteen different HA-NA combinations are known to cause human infections, studies have shown that Influenza H1N1, H1N2, and H3N2 HA-NA combinations have emerged multiple times since the Spanish flu pandemic that ravaged the world in 1918.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Annually, influenza A virus (IAV) infects~5-10% of adults and 20-30% of children worldwide, resulting in up to 650,000 deaths each year [1][2][3]. The ability of IAV to mutate, reassort, and infect multiple hosts results in a diverse viral population that causes annual epidemics and occasionally pandemic outbreaks.…”
Section: Introductionmentioning
confidence: 99%